IMPROVING STUDENTS' UNDERSTANDING OF BASIC ECONOMIC CONCEPTS AND ENTREPRENEURIAL SPIRIT THROUGH THE BUYING AND SELLING GAME SIMULATION METHOD AT CITRA KASIH SCHOOL - Winanto Poernomo; Windy Eka Saputri; Pandu Adi Cakranegara; Tutur Wicaksono (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
One of the things that educational institutions, especially universities, can contribute is human resources. The human resources that need to be prepared are not only those who are ready to work but also those who are ready to create jobs and work by providing added value. Entrepreneurship education from an early age is an important foundation for building a generation that is creative, innovative, and financially independent. Although entrepreneurship education is very important, economics education at the school level is often theoretical and lacks practical experience. This is understandable because of the tasks and demands of the curriculum. This is precisely where universities have an important role to play as centers of knowledge distribution to spread the spirit of entrepreneurship. Community service activities are designed to provide practical understanding of basic economic concepts—such as capital, production, buying and selling, and competition—to students at Citra Kasih School. The activity was held on Thursday, September 19, 2025, from 9:00 to 10:00 a.m. The method used was a buying and selling simulation game with a role-playing approach. Students were divided into four roles: Seller, Buyer, Supplier, and Observer. The results of the activity showed high enthusiasm from all participants. Through the simulation, students directly experienced the challenges of managing capital, developing sales strategies, and facing market competition. It was found that not all sellers succeeded in selling their products, which was an important learning point about market dynamics. This activity succeeded in increasing students' understanding of economic transaction flows and fostering a healthy competitive spirit.